2004
DOI: 10.1002/j.2161-0045.2004.tb00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Factors Associated With Sixth‐Grade Adolescents' Math and Science Career Interests

Abstract: This study tested a causal model, based on social cognitive career theory (SCCT; R. W. Lent, S. D. Brown, & G. Hackett, 1994, 2000), of math and science career interests among 6th‐grade adolescents (N = 318). Consistent with SCCT, it was found that career gender‐typing, mother's and father's support for pursuing math and science careers, as well as the structure of the family itself (2‐parent intact vs. single parent) predicted young adolescents' math self‐efficacy; career gender‐typing and mother's support pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
118
2
10

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(137 citation statements)
references
References 34 publications
(27 reference statements)
7
118
2
10
Order By: Relevance
“…La segunda hipótesis (H2.O2) también se verifi có puesto que el modelo SCCT se ajustó correctamente en la población global de estudiantes de bachillerato científi co-tecnológico. De forma similar a los resultados obtenidos en otras investigaciones, se subraya la infl uencia de las creencias de autoefi cacia en las expectativas de resultado, el interés y en las metas de los estudiantes del bachillerato científi co-tecnológico (Cupani & Lorenzo, 2010;Fouad & Smith, 1996;Lent et al, 2003;Lent et al, 2010;Turner et al, 2004). Nuestro estudio también corrobora el papel de las expectativas de resultado como variable predictora del interés y las metas.…”
Section: Discusión De Resultados Y Conclusionesunclassified
See 3 more Smart Citations
“…La segunda hipótesis (H2.O2) también se verifi có puesto que el modelo SCCT se ajustó correctamente en la población global de estudiantes de bachillerato científi co-tecnológico. De forma similar a los resultados obtenidos en otras investigaciones, se subraya la infl uencia de las creencias de autoefi cacia en las expectativas de resultado, el interés y en las metas de los estudiantes del bachillerato científi co-tecnológico (Cupani & Lorenzo, 2010;Fouad & Smith, 1996;Lent et al, 2003;Lent et al, 2010;Turner et al, 2004). Nuestro estudio también corrobora el papel de las expectativas de resultado como variable predictora del interés y las metas.…”
Section: Discusión De Resultados Y Conclusionesunclassified
“…De este modo, si una persona aprecia las consecuencias positivas que tiene para su desarrollo académico la realización de asignaturas tecnológicas, tendrá más interés por estas materias y persistirá con más ahínco para lograr el éxito en ellas. Asimismo, también se verifi ca que el interés por la tecnología infl uye en la aspiración de continuar en este tipo de materias (Cupani & Lorenzo, 2010;Fouad & Smith, 1996;Lent et al, 2003;Lent et al, 2010;Navarro et al, 2007;Turner et al, 2004).…”
Section: Discusión De Resultados Y Conclusionesunclassified
See 2 more Smart Citations
“…Jackson (2010) found that many of the females interviewed credited parental influence as having an impact on their overall perception and experiences in STEM areas. Turner, Steward, and Lapan (2004) found that support of both mother and father affected the mathematics selfefficacy of middle school students. Also, the support of mothers and fathers was significant in building the belief that mathematics was suitable for them (Turner et al, 2004).…”
Section: Homementioning
confidence: 99%